2014
DOI: 10.1111/ajt.12786
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Risk of Incompatible Kidney Transplantation: A Multicenter Study

Abstract: Incompatible live donor kidney transplantation (ILDKT) offers a survival advantage over dialysis to patients with anti‐HLA donor‐specific antibody (DSA). Program‐specific reports (PSRs) fail to account for ILDKT, placing this practice at regulatory risk. We collected DSA data, categorized as positive Luminex, negative flow crossmatch (PLNF) (n = 185), positive flow, negative cytotoxic crossmatch (PFNC) (n = 536) or positive cytotoxic crossmatch (PCC) (n = 304), from 22 centers. We tested associations between D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
144
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(157 citation statements)
references
References 36 publications
4
144
1
Order By: Relevance
“…(73). In a recent study of Orandi et al (74), mortality after kidney transplantation 5-year unadjusted mortality ranged between 9.3% and 19.1% depending on antibody-related graft compatibility.…”
Section: Discussionmentioning
confidence: 94%
“…(73). In a recent study of Orandi et al (74), mortality after kidney transplantation 5-year unadjusted mortality ranged between 9.3% and 19.1% depending on antibody-related graft compatibility.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have shown that DSA assessments using MFI alone may not be sufficient for assessing the potential risk for graft damage and decreased survival. Multiple assays are used, such as Flow‐XM,21, 27 C1q‐SAB assays,17 C3d‐SAB assays,28 or IgG‐subclass analysis 29. Our cohort includes 63 patients participating in the Eurotransplant Acceptable Mismatch program with an HLA antibody profile based on CDC, in some cases supplemented with solid phase assays 30.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we could find, there were no large cohorts describing the effect of pretransplant DSAs with negative CDC‐XM in exclusively living donor kidney transplants without desensitization treatment. Orandi et al21 studied the outcomes of incompatible living donor kidney transplants based on the risk determined by using the SAB assay, flow cytometry crossmatch (FCXM), or CDC‐XM and found that patients with a positive SAB assay and a negative FCXM (n = 185) who were desensitized had similar graft survival as a large group of compatible patients (n = 9669), while patients with a positive FCXM (n = 536) or a positive CDC‐XM (n = 304) experienced an increased risk of graft loss. Another study about living donor transplants performed after a positive FCXM (n = 41) reported that the long‐term survival was worse in desensitized recipients compared with matched recipients with a negative FCXM (n = 41) 22…”
Section: Introductionmentioning
confidence: 99%
“…This manuscript follows a similar pattern as others reporting the results of recent desensitization trials (2). That is, it fails to acknowledge that, since December 4, 2014, the kidney allocation system (KAS) prioritizes highly sensitized patients and hence, has dramatically reduced the mean waiting time for an organ offer (3).…”
mentioning
confidence: 85%